Demographic determinants of drug addiction in Algerian society An analytical statistical study based on data from the National Office for the Fight against Drugs and Drug Addiction (2012–2022) - Gouarah, Yamina; Bougrouz, Amina (Journal of Ecohumanism, 2025)
Drug addiction is a complex social phenomenon that poses a multi-dimensional challenge. Given the threat it poses to individual safety and the stability of Algerian society, this study analyzes the demographic determinants associated with this phenomenon and examines the extent of addiction in Algerian society, based on data from the National Office for the Fight against Drugs and Drug Addiction for the period 2012–2022.The study focuses on the main demographic determinants contributing to addiction namely gender, age, marital status, and occupational status.The research reached several conclusions, the most important of which are: the number of cases related to trafficking, possession, and consumption increased, with the total number of recorded cases rising to more than eight times its original figure, and the number of people involved increasing by over 570%.Regarding demographic determinants, the study revealed a gender disparity in drug addiction, with higher prevalence among men; however, in recent years, a rapid increase in addiction rates among women has been recorded. The phenomenon is most widespread among youth aged 16 to 35, with a worrying increase among children under 15. Higher rates of addiction are recorded among single and unemployed individuals, with a noticeable rise among students in recent years.The data also indicate the predominance of cannabis and psychotropic substances among the most addictive drugs, along with the emergence of multiple forms of addiction reflecting the complexity of the phenomenon and the diversity of its behavioral patterns.